Reactive agility of U19 female basketball players and its relationship with speed and power - Vencúrik, T.; Bokuvka, D.; Petru, J.; Michaelides, M.; Parpa, K.; Carolina, A. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
This study aimed to find a relationship between the reactive agility of U19 female basketball players and speed and power characteristics. This study involved twelve U19 female basketball players from the first division who participated in various tests aimed at evaluating different aspects of their physical performance. These tests included assessments of power through the squat jump, countermovement jump, and drop jump, linear speed through 5, 10, and 20-meter sprints, change of direction speed through the 505 test, and reactive agility through the Y-shaped test. The correlation coefficient showed a large association (r = 0.64, p = 0.02) between the Y-shaped test and the 20 m linear sprint. The Association of the Y-shaped test with other power and speed tests was small or moderate. These findings suggest that basketball coaches working with young female players can leverage the enhancement of reactive agility to concurrently develop linear speed.